Emission of nitrous oxide in flooded rice cultivation in tropical area of Brazil - Mascarenhas, Yoná Serpa; Silva, Melissa Ananias Soler da; Correchel, Vládia; Santos, Alberto Baêta dos; Carvalho, Márcia Thaís de Melo; Madari, Beáta Emöke; Coelho, Alexandre Siqueira; Gonçalves, Gustavo Melo de Oliveira; Caetano, Pedro Henrique Pereira (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the effects of nitrogen fertilizers on the N dynamics and grain yield in flooded rice (Oryza sativa) cultivation in Brazilian tropical wetland. The experiment was carried out in a randomized complete block design with six treatments, as follows: common and protected urea; topdressing application of N doses (30, 70, and 150 kg ha-1); and one control treatment, without N fertilization. Emissions of N2O-N, global warming potential (pGWP), emission factors (EF) for mineral fertilizers, grain yield, emission intensity, nitrate, ammonium, pH, and potential redox were quantified. Gas sampling was carried out in two crop seasons of rice cultivation and in one off-season. During the flooded period of the two crop seasons, N2O fluxes did not exceed 862.41 μg m-2 h-1 N2O-N; in the off-season, the fluxes varied from -52.95 to 274.34 μg m-2 h-1 N2O-N. Consistent emission peaks were observed in soil draining before harvest, when the highest rate of both N sources was used, and also in the control treatment in the off-season. Protected urea does not reduce N2O emissions or EF. Nitrogen increases the grain yield. Protected urea does not have any effect on the pGWP. The concentrations of NO3- and NH4+ in the soil are not related to N2O fluxes.